Understanding Interpreting Strategies: Case Study in Consecutive Interpreting in Jokowi and Malcolm Turnbull Press Conference - Hastuningdyah, Wikan (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
The most important duty of a translator and an interpreter is to deliver the message from the SL to TL. Differs from a translator, an interpreter works in a limited time span and will rely on the knowledge and vocabulary he/she knows beforehand in order to deliver the meaning of the speech. Therefore, an interpreter should implement various forms of interpreting techniques, as stated by Li (2015) that strategies are tools for interpreters to overcome challenges in interpreting. The research material of this paper is the President of Republic of Indonesia, Mr. Joko Widodo and Prime Minister of Australia, Mr. Malcolm Turnbull Press Conference on February 2017. The press conference was done by consecutive interpreting. This study is conducted in qualitative approach by Hale and Napier (2013) to show the concept and characteristic of the strategies used in the interpretation and to analyze process and product of interpreting. As result it is found that both of interpreters applied strategy to enhance their understanding of the message and to overcome of the difficulty of the speech and the short time span. The most frequent strategies applied by both of interpreters are transcoding, omission and addition.